The Benefits of The Asynchronous Online Learning Model at Post-Pandemic Covid-19: Students’ Perception - Geminastiti Sakkir; Ice Trisnawati; Auliyanti Sahril Nurfadhilah (ELT Worldwide: Journal of English Language Teaching, 2023)
In the rapidly evolving landscape of education, asynchronous online learning has emerged as a significant model, offering students the flexibility to access materials and lectures at their convenience. This research aimed to delve deeper into students' perceptions of the benefits of the asynchronous online learning model at Institut Parahikma Indonesia, a prominent educational institution. Employing a qualitative descriptive approach complemented by a phenomenological design, the study sought to capture the lived experiences and nuanced views of students regarding this learning model. Data were meticulously gathered through semi-structured interviews, ensuring a comprehensive understanding of students' perspectives. A total of seven respondents participated, comprising three males and four females from Institut Parahikma Indonesia. These participants were selected using a convenience sampling method, providing a diverse range of insights. The findings of this study were illuminating. Students predominantly perceived the asynchronous learning model as beneficial, highlighting aspects such as motivated learning, insightful experiences, flexibility in managing their time, and the advantage of accessing easier-to-understand material. They appreciated the ability to learn at their own pace, revisit lectures, and balance their studies with other commitments. However, it's noteworthy that not all feedback was overwhelmingly positive. A segment of students expressed a longing for direct, synchronous interactions, indicating a preference for traditional learning dynamics. The present study offers a fresh perspective on the asynchronous online learning model, emphasizing its benefits while also shedding light on areas of potential improvement. The insights garnered hold significant implications for educational institutions, policymakers, and educators, urging them to consider a more blended approach that caters to the diverse needs of students.